Euophryine jumping spiders of the Afrotropical Region—new taxa and a checklist (Araneae: Salticidae: Euophryinae) - Wesołowska, Wanda; Azarkina, Galina N.; Russell-Smith, Anthony (Zootaxa, 2014)
Two new genera, Rumburak gen. nov. and Yimbulunga gen. nov., of euophryine jumping spiders are established from the Afrotropical Region. Thirty three new species included in this subfamily are diagnosed and described: Chinophrys trifasciata sp. nov. (♂, South Africa), Euophrys bifida sp. nov. (♂♀, South Africa), E. cochlea sp. nov. (♂♀, South Africa), E. elizabethae sp. nov. (♂♀, South Africa), E. falciger sp. nov. (♂♀, South Africa), E. gracilis sp. nov. (♂♀, Lesotho, South Africa), E. griswoldi sp. nov. (♂, Namibia), E. limpopo sp. nov. (♂, South Africa), E. maseruensis sp. nov. (♂, Lesotho), E. meridionalis sp. nov. (♂♀, South Africa), E. miranda sp. nov. (♀, South Africa), E. nana sp. nov. (♂, South Africa), E. recta sp. nov. (♂, South Africa), E. subtilis sp. nov. (♂♀, South Africa), Rumburak bellus sp. nov. (♂, South Africa), R. hilaris sp. nov. (♂♀, South Africa), R. lateripunctatus sp. nov. (♂♀, South Africa), R. mirabilis sp. nov. (♂♀, South Africa), R. tuberatus (♂, South Africa), R. virilis (♂♀, South Africa), Tanzania parvulus sp. nov. (♂♀, South Africa), T. striatus sp. nov. (♂♀, South Africa), Thyenula alotama sp. nov. (♂♀, South Africa), T. cheliceroides sp. nov. (♂, South Africa), T. clarosignata sp. nov. (♂♀, South Africa), T. dentatidens sp. nov. (♂, South Africa), T. haddadi (♂♀, South Africa), T. montana sp. nov. (♂, Lesotho), T. rufa sp. nov. (♂♀, South Africa), T. tenebrica sp. nov. (♀, South Africa), T. virgulata sp. nov. (♂, South Africa), T. vulnifica sp. nov. (♂♀, South Africa) and Yimbulunga foordi sp. nov. (♂, South Africa). Two species names are newly synonymized: Thyenula hortensis Wesołowska & Cumming, 2008 with T. munda (Peckham & Peckham, 1903) and Thyenula nelshoogte Zhang & Maddison, 2012 with T. laxa Zhang & Maddison, 2012.  Three new combinations are proposed: Heliophanus kittenbergeri (Caporiacco, 1947) (ex Euophrys), Rumburak laxus (Zhang & Maddison, 2012) (ex Thyenula) and Thyenula munda (Peckham & Peckham, 1903) (ex Saitis). Two names are recognized as nomina dubia: Euophrys nigrescens Caporiacco, 1940 and Saitis magnus Caporiacco, 1947. The first member of the genus Chinophrys Zhang & Maddison, 2012 is reported from Africa. The males of Euophrys leipoldti Peckham & Peckham, 1903 and Thyenula sempiterna Wesołowska, 2000 are described for the first time. Tanzania minutus (Wesołowska & Russell-Smith, 2000) is recorded from South Africa for the first time. A list of valid species of Afrotropical Euophryinae with data on their distribution in the region is provided. A key is supplied for the known genera of the region (based on males).